1970
DOI: 10.1002/1097-4679(197004)26:2<152::aid-jclp2270260205>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of projection as a defense mechanism

Abstract: PROBLEMWhile projection is one of the oldest concepts in psychology, reviews such as those of Campbell et U Z (~) and Murstein et uZ(') reveal that experimental evidence regarding this concept is limited and often of an uncontrolled, anecdotal sort. This concept has high clinical utility which could be increased with controlled empirical information. This study experimentally investigated the defensive aspect of projection with special attention given to its often claimed anxiety-reducing property. METHOD Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1975
1975
1988
1988

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…This is consistent with the findings of Houston (1971Houston ( , 1973, Houston and Hodges (1970), and Lazarus and Alfert (1964), who reported the advantage of denial in stressful situations and the arousal-reducing qualities of denial and reaction formation (reversals). The present findings are supportive of Bennett and Holmes (1975), who reported a reduction in arousal relating to projection, but are in contrast to Holmes and Houston (1971) and Stevens and Reitz (1970), who did not support the projection/anxiety reduction hypothesis. The reversal defensive mechanisms of the DMI include denial, reaction formation, and negation.…”
Section: Cognitive Reappraisals/defense Mechanismssupporting
confidence: 53%
“…This is consistent with the findings of Houston (1971Houston ( , 1973, Houston and Hodges (1970), and Lazarus and Alfert (1964), who reported the advantage of denial in stressful situations and the arousal-reducing qualities of denial and reaction formation (reversals). The present findings are supportive of Bennett and Holmes (1975), who reported a reduction in arousal relating to projection, but are in contrast to Holmes and Houston (1971) and Stevens and Reitz (1970), who did not support the projection/anxiety reduction hypothesis. The reversal defensive mechanisms of the DMI include denial, reaction formation, and negation.…”
Section: Cognitive Reappraisals/defense Mechanismssupporting
confidence: 53%
“…No studies, for example, have looked at the self-serving effects of classical projection. Holmes (1978) reviewed six studies (Bennett & Holmes, 1975;Holmes & Houston, 1971;Stevens & Reitz, 1970;Zemore & Greenough, 1973; Burish, Note 2; Hellman & Houston, Note 3) and concluded that "there does not appear to be any consistent or reliable evidence that projection of undesirable traits reduces stress as assessed by self-report, physiological, or performance measures" (p. 686). I do not believe this conclusion to be justified.…”
Section: Defensive Function Of Projectionmentioning
confidence: 99%
“…Although a substantial amount of research suggests that people do in fact employ similarity projection (cf. Holmes, 1968), relatively few experiments have been carried out to answer the question of whether similarity projection reduces stress, and the work which has been done (Bennett & Holmes, 1975;Halpern, 1977;Holmes & Houston, 1971;Stevens & Reitz, 1970) has produced mixed results, frequently within the same experiment. Again, it may be that previous research has failed to provide the conditions under which projection is most likely to exert a stress-reducing effect.…”
mentioning
confidence: 99%